2023
DOI: 10.3390/ijms241411857
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Quercetin by Selected Entomopathogenic Filamentous Fungi and Prediction of Its Products’ Bioactivity

Abstract: Quercetin is the most abundant flavonoid in food products, including berries, apples, cauliflower, tea, cabbage, nuts, onions, red wine and fruit juices. It exhibits various biological activities and is used for medical applications, such as treating allergic, inflammatory and metabolic disorders, ophthalmic and cardiovascular diseases, and arthritis. However, its low water solubility may limit quercetin’s therapeutic potential. One method of increasing the solubility of active compounds is their coupling to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Due to the large number of compounds formed, attempts to isolate them were not pursued. Nevertheless, the obtained result indicates that the tested biocatalyst produces a multitude of enzymes capable of transforming steroid compounds and indicates the possibility of using this strain in the biocatalysis of various bioactive compounds; e.g., in our previous work, we described the effective glycosylation of quercetin by Isaria tenuipes MU35 [ 52 ]. It was also proven that a strain of this species is capable of an effective metabolism of zearalenone and, similar to the two representatives of this genus more popular in biocatalysis ( I. fumosorosea , I. farinosa ), multienzymatic transformations of the used substrate were observed [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the large number of compounds formed, attempts to isolate them were not pursued. Nevertheless, the obtained result indicates that the tested biocatalyst produces a multitude of enzymes capable of transforming steroid compounds and indicates the possibility of using this strain in the biocatalysis of various bioactive compounds; e.g., in our previous work, we described the effective glycosylation of quercetin by Isaria tenuipes MU35 [ 52 ]. It was also proven that a strain of this species is capable of an effective metabolism of zearalenone and, similar to the two representatives of this genus more popular in biocatalysis ( I. fumosorosea , I. farinosa ), multienzymatic transformations of the used substrate were observed [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
“…The microorganisms Beauveria bassiana KCh J1.5, B. caledonica KCh J3.3, Isaria farinosa KCh KW 1.1 and I. fumosorosea KCh J2, and Metarhizium robertsii MU4 and Isaria tenuipes MU35 were obtained from the collection of the Department of Food Chemistry and Biocatalysts, at the Wrocław University of Environmental and Life Sciences (Wrocław, Poland) and the collection of the Institute of Plant Genetics, at the Polish Academy of Sciences (Poznań, Poland). Isolation and identification procedures were described in our previous papers [ 36 , 52 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin consists of five hydroxyl groups ( Figure 2 ), which determine the biological activity of the compound [ 2 , 12 ]. Naturally, quercetin is distributed in the form of derivatives, either in glycosidic form, mainly attached to the C-3 carbon with glucose, rhamnose, and rutinose, or linked to others, and it is very rarely distributed as an aglycone [ 13 ]. On the other hand, quercetin in its aglycone form is a bright lemon-yellow powder, insoluble in water but soluble in alcohol and lipids.…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…It usually is more soluble, more stable, and more functional compared to their aglycones [67]. Furthermore, some research has demonstrated that the glycosylation of flavonoids had shown higher antioxidant activities; stronger hepato-, cardio-, and vasoprotectant behavior; and free radical scavengers than aglycone [68,69].…”
Section: Improving Intracellular Udp-sugar Level For Biosynthesis Of ...mentioning
confidence: 99%